Digital assets and their legal treatment at the national level from the perspective of private law (Forseti. Law Review, 2025)
This paper presents a comparative analysis of the regulatory evolution of digital assets, with a focus on tokens, and proposes a legal approach from the perspective of Peruvian Private Law to address their treatment within the national legal framework.
Keywords: Digital assets; Intangible goods; Comparative law; Peruvian law; Regulation; Blockchain; Capital markets